2020
DOI: 10.1038/s41598-020-64625-w
|View full text |Cite
|
Sign up to set email alerts
|

Structure evolution during deposition and thermal annealing of amorphous carbon ultrathin films investigated by molecular dynamics simulations

Abstract: The evolution of the structure of amorphous carbon (a-C) films during deposition and thermal annealing is of significant interest from both the materials science and application perspectives. However, despite the voluminous literature of studies dealing with the deposition and physical properties of a-C films, basic understanding of the structure evolution due to phase change during film growth and heating is fairly sparse and empirical, presumably due to the lack of high-resolution instruments that can probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
(49 reference statements)
3
19
0
Order By: Relevance
“…Carbon is a prime example: different routes to computationally generate ta-C structures have been explored * mcaroba@gmail.com in detail, the most popular being the "liquid quench" technique [10][11][12][13][14][15][16]. Explicit deposition of carbon atoms [17][18][19][20][21][22][23][24][25][26], mimicking ta-C film growth under experimental conditions, is too computationally costly to be practical at the DFT level. Alternative generation techniques, including quenching from the simulated melt, invariably fall short, each to a different extent, of predicting experimental sp 3 values [27], which can be as high as 90% for "superhard" ta-C [28].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon is a prime example: different routes to computationally generate ta-C structures have been explored * mcaroba@gmail.com in detail, the most popular being the "liquid quench" technique [10][11][12][13][14][15][16]. Explicit deposition of carbon atoms [17][18][19][20][21][22][23][24][25][26], mimicking ta-C film growth under experimental conditions, is too computationally costly to be practical at the DFT level. Alternative generation techniques, including quenching from the simulated melt, invariably fall short, each to a different extent, of predicting experimental sp 3 values [27], which can be as high as 90% for "superhard" ta-C [28].…”
Section: Introductionmentioning
confidence: 99%
“…The overall sp 3 content of the a -C film was varied by changing the kinetic energy of the incident carbon atoms. Additional details about the MD model of ultrathin a -C film growth used in this study can be found elsewhere 22 .…”
Section: Computational Proceduresmentioning
confidence: 99%
“…An elevated temperature may destabilize the microstructure and degrade the properties of a -C films by promoting sp 3 -to- sp 2 rehybridization, consequently lessening the film’s ability to effectively protect the substrate material 18 , 19 . Experimental and computational studies have revealed the existence of a threshold temperature in the range of 200–350 °C above which a -C films undergo significant structural changes 20 22 . Increasing the sp 3 fraction and doping with certain elements, such as silicon, have been proven effective methods for enhancing the thermal stability of a -C films by stabilizing the carbon atoms in the sp 3 hybridization state and inhibiting sp 3 -to- sp 2 rehybridization at high temperatures 23 – 25 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations